Performing comprehensive nutrient recovery through the integration of selective electrodialysis with reverse osmosis by using synthetic swine wastewater - Jingwei Xu; Yahui Huang; Zhi-Long Ye; Xiaofang Pan; Yenan Li; Lifeng Lin (Desalination, 2026)

A membrane-anchored nanoscale zero-valent iron bio-interface enhances interspecies electron transfer in anaerobic membrane bioreactors - Mingchao Zhu; Huilai Zhang; Lin Zhang; Shuping Li; Shouwen Chen; Zhaoxia Hu; Jingwei Wang; Na Li; Yongze Lu (Bioresource Technology, 2026)

Model test study of polyurethane grouting repair for gas pipelines in mining subsidence areas - Du Zibo; Tian Haodong; Ma Zhanguo; Li Lin; Zhang Jingwei; Zhou Chuang (Tunnelling and Underground Space Technology, 2026)

Optimizing carbon-cement electrode performance through construction of a strong skeleton-highly connected pore structure based on ettringite - Xiang Lin; Xujiang Wang; Guanjie He; Jian Song; Yanmei Cheng; Jie Chen; Xin Shu; Deqiang Sun; Jingwei Li; Zhijuan Hu; Wenlong Wang (Chemical Engineering Journal, 2026)

Static magnetic field-assisted fermentation of corn dietary fiber by Hericium erinaceus: Insight into fermentation mechanisms and related characteristics - He Ban; Jingwei Wang; Ding Xu; Xiangmeng Yin; Wei Li; Lin Xiu; Dan Cai; Jingsheng Liu (Food Chemistry, 2026)

Ameliorating ischemic stroke by systematically screening natural polyphenols to counteract the dual effects of AMPK activation in microglia - Jingwei Liu; Jian Wang; Huan Liu; Luyao Zhu; Kang Li; Qiangfei Su; Dan Luo; Tao Guo; Zheng Wang; Lin Wang (Chemical Engineering Journal, 2026)

A LINE-1 retrotransposon promotes SEMA3C expression as a cis-regulatory enhancer to sustain breast cancer stem cell survival - Qidong Xia; Jingwei Feng; Jiayao Pan; Wen Deng; Xiaoqi Weng; Jianhui Jiang; Lin Wang; Wenqian Xie; Yi Chen; Aiwei Bi; Jiang Li; Yiwen Lu; et al. (Science China Life Sciences, 2026)

Gypenosides as a potential bacteriostatic agent against Escherichia coli: dual mechanistic insights from host target network analysis and in vitro validation - Jingwei Pan; Runcheng Zhou; Wenjing Zhang; Kecan Chen; Jiaxi Liang; Jiahao Shen; Zhiteng Lin; Xumei Yi; Shanfan Weng; Xin Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Transferable prediction of TBM long-distance tunneling construction duration considering uncertainties in surrounding rock distribution and the evolution of tunneling efficiency - Jianming Zhang; Kebin Shi; Peixuan Lin; Lei Li; Qiyong Mao; Haibo Jiang; Xinjun Yan; Jingwei Gong (Tunnelling and Underground Space Technology, 2026)

Static magnetic field assists corn germination: Changes in nutritional composition and improvement of functional properties - Xin Jiang; Yelinxin Chen; Xiaoxi Yu; Jingwei Wang; Ding Xu; Huimin Liu; Dan Cai; Lin Xiu; Jingsheng Liu (Food Chemistry, 2026)

Environmental risks and upcycling potential in ternary geopolymer development for oily sludge pyrolysis byproducts - Chenxu Zhong; Chujun Luan; Xuan Guo; Fawei Lin; Jingwei Li; Beibei Yan; Zhanjun Cheng; Eminov Ashraf Mamurovich; Bigaliev Aitkhazha Bigalievich; Guanyi Chen (Journal of Environmental Chemical Engineering, 2026)

Thin film nanocomposite membrane incorporated with sulfonic acid-based HOFs for efficient reverse osmosis desalination - Yu-ting Liu; Zi-yue Tang; Zi-ao Zong; Wan-zhen Wang; Xiao-yin Zhang; Xin-ping Song; Xiang-min Meng; Rijia Lin; Jingwei Hou (Desalination, 2026)

Self-cleaning nanofiber membrane for efficient oil-water separation and dye degradation - Hai-chao Bai; Zi-yue Tang; Zi-ao Zong; Xin-ping Song; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Rijia Lin; Jingwei Hou (Journal of Cleaner Production, 2026)

The value assessment framework and institutional innovation for implementing the requisition-compensation balance policy of natural coastline in China - Yue Yu; Yanyan Fu; Wei Liu; Degang Jiang; Jingwei Zhang; Xingmin Liu; Xueping Wei; Jing Lin (Frontiers in Marine Science, 2026)
Natural coastlines are vital for ecological security and sustainable development. To mitigate their decline, China has implemented requisition-compensation balance policy (RCBP) for coastlines, adapted from the management of cultivated land. This study systematically reviews the policy’s institutional evolution and highlights fundamental distinctions between coastlines and cultivated land in functional services, spatial heterogeneity, and evaluation standards. While the policy has achieved preliminary success in maintaining quantitative and qualitative balance, several challenges persist. These include the absence of functional equivalence assessment, weak long-term safeguards, underdeveloped cross-regional and market-based coordination mechanisms. These gaps risk leading to “higher-grade requisition, lower-grade compensation” and ecological degradation at compensation sites, and increased administrative burdens. To address these issues, this study develops a comprehensive value-equivalence compensation framework structured around a “three-dimensional and four-layer” indicator system that integrates functional, spatial, and temporal dimensions. It advocates for a strategic transition from quantity-oriented to value-oriented governance. Corresponding policy recommendations are proposed: establishing unified technical guidelines for value assessment, creating a nationwide quota-trading platform to activate market forces, and strengthening post-restoration monitoring for long-term stewardship. This research provides theoretical and practical insights to enhance the protection, restoration and sustainable management of coastlines in China.

Evaluation of the multi-scale variability of ocean bottom pressure in a global ocean general circulation model - Jiahui Bai; Jingwei Xie; Zipeng Yu; Jiangfeng Yu; Hailong Liu; Fan Yang; Pengfei Lin; Tao Zhang; Chunxiang Shi; Yun Xiao (Acta Oceanologica Sinica, 2026)

Unveiling mechanisms governing heavy metal leaching from solid waste-vitrified glasses for cleaner resource recovery - Xinyue Wang; Jiayong Li; Jie Chen; Xunchang Fei; Weiqin Zeng; Jingwei Li; Zhiliang Chen; Xiaoqing Lin (Journal of Cleaner Production, 2026)

Atomic dispersion of scandium in electrochemically reduced copper oxide nanosheets for efficient electrocatalytic CO2 reduction to C2+ products - Yang Zhao; Binwen Zeng; Haoliang Huang; Huanhuan Yang; Zhipeng Yu; Chao Song; Jingwei Wang; Kaiyang Xu; Xinyi Xiang; Wei Wang; Fei Lin; Sheng Meng; et al. (Chemical Engineering Journal, 2025)

Exogenous plastic stress: polypropylene-induced phenotypic alterations and oxidative stress adaptation in Pseudomonas aeruginosa - Wenjing Zhang; Runcheng Zhou; Jingwei Pan; Zhiteng Lin; Xumei Yi; Kecan Chen; Xin Chen (Antonie van Leeuwenhoek, 2025)

Complete nitrogen removal via novel nitrite-absent anodic anammox process with granular sludge in titanium anode microbial electrolysis cells - Liang Zhu; Jingwei Ma; Zhanhang Wang; Ying Han; Long Chen; Hui Sun; Qiulai He; Lin Deng; Zhou Shi; Shuizhou Ke (Chemical Engineering Journal, 2025)

Self-cleaning nanofiber membranes for sustainable dual removal of oils and dyes from wastewater - Hai-chao Bai; Yu-kun Sun; Zi-yue Tang; Zi-ao Zong; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Jingwei Hou; Rijia Lin (Chemical Engineering Journal, 2025)

Exploration on using solid waste-derived sulphoaluminate composite as low-cost binder for high-impermeability stabilization of sandy soil - Shuang Zhang; Jingwei Li; Wenbin Shi; Fawei Lin; Bigaliev Aitkhazha Bigalievich; Eminov Ashraf Mamurovich; Wenlong Wang (Waste Disposal & Sustainable Energy, 2025)

Nitrogen fertilization management is required for soil phosphorus mobilization by phoD-harboring bacterial community assembly and pqqC-harboring bacterial keystone taxa - Lin YANG; Runze WANG; Jingwei SHI; Rui WANG; Shengli GUO (Pedosphere, 2025)

The simulation of the South China Sea by the variable resolution version of the global ocean general circulation model LICOM3.0 - Jiangfeng Yu; Jingwei Xie; Hailong Liu; Pengfei Lin; Zipeng Yu; Jiahui Bai (Ocean Modelling, 2025)

Liquid–liquid phase separation in normal hematopoiesis and hematological diseases - Lexuan Lin; Fang He; Xu Jin; Xiaoru Zhang; Yue Li; Di Wang; Jingwei Wang; Lingyue Zheng; Haoze Song; Xu Zhu; Qimei Cheng; Yitong Zhao; et al. (Cell and Tissue Research, 2025)

Global Change Modulates Microbial Carbon Use Efficiency: Mechanisms and Impacts on Soil Organic Carbon Dynamics - Jingwei Shi; Lei Deng; Jianzhao Wu; Yuanyuan Huang; Yajing Dong; Josep Peñuelas; Yang Liao; Lin Yang; Xingyun Huang; Hailong Zhang; Jiwei Li; Zhouping Shangguan; et al. (Global Change Biology, 2025)
Microbial carbon use efficiency (CUE) is a key parameter of initial microbial utilization of organic matter in soil. The responses of CUE to global change factors (GCFs) remain unclear due to their multiple effects and interactions. Here, this study generalized 385 observations obtained using various methods, including 13 C‐/ 14 C‐labeled substrates, 18 O‐labeled water, stoichiometric modeling, and others. The effects of climate change (drought, precipitation, warming), fertilization (nitrogen addition, phosphorus addition, potassium addition, and nitrogen fertilization combined with phosphorus and potassium), land use conversion, and natural restoration, were evaluated along with their 16 associated GCFs on CUE. CUE was insensitive to climate change factors and most fertilization practices, maintaining a mean value of 0.36 under global change scenarios. Farmland conversion to forest and vegetation restoration decreased CUE by 11% and 17%, respectively. Grassland restoration increased CUE by 41%, indicating that grasslands have high potential for soil carbon accrual. Nitrogen fertilization combined with phosphorus and potassium increased CUE by 18% because the combined application of nutrients allows plants to produce organic matter sources with high‐quality and decreases nutrient limitations for microorganisms. Increase in soil pH induced by GCFs leads to higher CUE. The CUE was decoupled from soil organic carbon content under several global change scenarios (e.g., warming, fertilization), suggesting that this relationship is not universally consistent across GCFs. This study provides a new perspective on the responses of CUE to GCFs and deepens our understanding of the global change effects on microbial physiology with consequences for soil carbon cycling.

Multi-timescale short-term urban water demand forecasting based on an improved PatchTST model - Peijie Lin; Xiangxin Zhang; Longcong Gong; Jingwei Lin; Jie Zhang; Shuying Cheng (Journal of Hydrology, 2025)

Three-dimensional nitrogen-doped modified activated carbon/graphene composite aerogel for highly efficient removal of indoor formaldehyde - Jingwei Xu; Mengyao Guo; Ming Lin; Chen Ma; Guohua Chen (Journal of Environmental Chemical Engineering, 2025)

Enzymatic degradation of polybutylene succinate by recombinant cutinase cloned from Paraphoma chrysanthemicola - Jingwei Lin; Kexin Sun; Li Ma; Chunwang Li; Haibin Tong; Zhanyong Wang (Journal of Environmental Management, 2025)

Decreased net N nitrification rate constrains soil N availability during long-term Camellia oleifera cultivation - Tinghao Zong; Jingwei Ma; Xinming Guan; Yusong Lin; Yuqi Chen; Meiqi Wang; Jiaze Lv; Yichao Rui; Yang Chen; Lichao Wu; Sheng Lu (Applied Soil Ecology, 2025)

Occurrence and ecological risk of disinfection byproducts in urban water body during the pandemic in the Pearl River Delta - Huazhi Wu; Lin Zhang; Pengran Guo; Yanping Zhao; Yumei Song; Xuerong Zhang; Yongqian Lei; Jingwei Xu (Journal of Hazardous Materials, 2025)

Surface in situ Co-Mn modification over LaMnO3 perovskite with enhanced activity for ethane combustion - Peng Zhao; Jingwei Liu; Wei Zhu; Jie Meng; Zhuang Li; Jinwei Qin; Xiaohui Wang; Haiqin Wan; Chao Yao; Lin Dong (Journal of Environmental Chemical Engineering, 2024)

A WUSCHEL-related homeobox transcription factor, SlWOX4, negatively regulates drought tolerance in tomato - Hui Li; Wanying Ma; Xiao Wang; Hongling Hu; Lina Cao; Hui Ma; Jingwei Lin; Ming Zhong (Plant Cell Reports, 2024)

Phenotypic and genetic effect of carotid intima-media thickness on the risk of stroke - Wenqiang Zhang; Jingwei Zhu; Xuan Wu; Tianle Feng; Wei Liao; Xuan Li; Jianci Chen; Li Zhang; Chenghan Xiao; Huijie Cui; Chao Yang; Peijing Yan; et al. (Human Genetics, 2024)

Deciphering microbial drivers of soil organic matter mineralization in surface and subsurface soil during long-term vegetation succession - Jingwei Shi; Lei Deng; Lin Yang; Yajing Dong; Yang Liao; Jiwei Li; Yurong Liu; Chengjie Ren; Feng Yang; Zhouping Shangguan; Yakov Kuzyakov (Agriculture, Ecosystems & Environment, 2024)

Sulfur and phosphorus co-doped FeCoNiCrMn high-entropy alloys as efficient sulfion oxidation reaction catalysts enabling self-powered asymmetric seawater electrolysis - Zhipeng Yu; Danil W. Boukhvalov; Hao Tan; Dehua Xiong; Chuangshi Feng; Jingwei Wang; Wei Wang; Yang Zhao; Kaiyang Xu; Weifeng Su; Xinyi Xiang; Fei Lin; et al. (Chemical Engineering Journal, 2024)

Honeycomb-like triazine-based conjugated microporous polymers exhibiting simultaneous and ultrasensitive detection of fifteen polycyclic aromatic hydrocarbons using solid-phase microextraction technique - Xinzhong Zhang; Hong Ji; Xuemei Wang; Lin Fan; Jingwei Liu; Wen Zhang; Xinzhen Du; Xiaoquan Lu (Analytica Chimica Acta, 2024)

Modification of coal gasification slag-based activated coke by KOH activation method and its adsorption performance on methyl orange - Xiaofang You; Lixin Song; Jingwei Wang; Jianqiao Lv; Liqing Sun; Lin Li; Meng He (Journal of Water Process Engineering, 2024)

Critical review for the potential analysis of material utilization from inorganic industrial solid waste - Xuan Guo; Menglan Zeng; Hongdi Yu; Fawei Lin; Jingwei Li; Wenlong Wang; Guanyi Chen (Journal of Cleaner Production, 2024)

Sodium alginate/graphene oxide (SA/GO) gel balls for Pb(II)-containing mine wastewater treatment: Molecular design and Pb(II) adsorption characteristics - Lin Li; Jingwei Wang; Mengyv Lin; Meng He; Xiaoru Wang; Xiaofang You (Journal of Water Process Engineering, 2024)

Effect of use of NSAIDs or steroids during the acute phase of pain on the incidence of chronic pain: a systematic review and meta-analysis of randomised trials - Luyao Huo; Gang Liu; Bowen Deng; Lin Xu; Yanjun Mo; Shengyuan Jiang; Jingwei Tao; Huizhong Bai; Li Wang; Xiaoxiao Yang; Jizhou Yang; Xiaohong Mu (Inflammopharmacology, 2024)
Background This study is the first to summarize the evidence on how the use of anti-inflammatory drugs during acute pain has an impact on the development of chronic pain. Methods Randomized controlled trials retrieved from nine databases included anti-inflammatory drugs (NSAIDs or steroids) versus non-anti-inflammatory drugs in patients with acute pain and reported the incidence of chronic pain. No specified date, age, sex, or language restrictions. Subgroup analyses were performed according to pain classification, follow-up time, and medication. The GRADE method was used to evaluate quality of evidence. Results A total of 29 trials (5220 patients) were included. Steroids or NSAIDs did not reduce the incidence of chronic nociceptive pain. Steroid use in acute phase significantly reduced the incidence of chronic neuropathic pain. In subgroup analysis, benefits were observed for methylprednisolone and dexamethasone, with some adverse effects. Steroids or NSAIDs were statistically significant in reducing pain intensity over 1 year, but the effect size was too small, and whether the long-term effect is clinically relevant needs to be further studied. Conclusion Quality of the evidence was low to moderate. No drug can be recommended to prevent chronic nociceptive pain. Injections of steroids (methylprednisolone or dexamethasone) during the acute phase reduce the incidence of chronic neuropathic pain, but most included studies also used local anesthetics. The results are indirect and need to be interpreted with caution. The pooled data effect sizes for pain intensity were small, so the clinical relevance was unclear. Study registration PROSPERO (CRD42022367030).

Ammonium enrichment, nitrate attenuation and nitrous oxide production along groundwater flow paths: Carbon isotopic and DOM optical evidence - Lin Zhang; Zhixin Zhang; Xin Huang; Jingwei Zhang; Uwe Schneidewind; Stefan Krause; Menggui Jin; Xing Liang; Hongbin Zhan (Journal of Hydrology, 2024)

Investigation on the preparation of coal slime flotation microemulsion collector: A combination of experimental and simulation method - Meng He; Jingwei Wang; Jida Niu; Hao Lyu; Liqing Sun; Xiaofang You; Lin Li; Qingbiao Wang (Fuel, 2024)

A materiobiology-inspired sericin nerve guidance conduit extensively activates regeneration-associated genes of Schwann cells for long-gap peripheral nerve repair - Xiakeerzhati Xiaohalati; Jian Wang; Qiangfei Su; Yang Wang; Jingwei Liu; Haozhe Li; Zheng Wang; Lin Wang (Chemical Engineering Journal, 2024)

Moderate input of nanoscale zero-valent iron accelerated soil polychlorinated biphenyls dissipation with limited inhibition on arbuscular mycorrhizal fungal diversity - Shuo Wen; Dongnian Sun; Hua Qin; Jingwei Wang; Xiangui Lin; Jianfeng Bai; Junli Hu (Journal of Soils and Sediments, 2024)

Identification a novel Ganoderma FIP gene from Ganoderma capense and its functional expression in Pichia pastoris - Jingwei Lin; Yating Liao; Sijia Yang; Taicheng Jin; Boning Yu; Kai Zhao; Yixiao Sai; Cheng Lin; Yanhua Song; Hui Ma; Zhanyong Wang (World Journal of Microbiology and Biotechnology, 2024)

Removal of multiple pollutants in air pollution control devices of a coal-fired boiler installed with a flue gas condensation scrubber - Tailin Chen; Lejun Deng; Yuzhong Li; Jingwei Li; Xiling Zhao; Lin Fu (Journal of Cleaner Production, 2024)

Recalcitrant organic carbon plays a key role in soil carbon sequestration along a long-term vegetation succession on the Loess Plateau - Jingwei Shi; Mingyang Song; Lin Yang; Fei Zhao; Jianzhao Wu; Jiwei Li; Zhijing Yu; Ao Li; Zhouping Shangguan; Lei Deng (CATENA, 2023)

An N-N linked dimeric indole alkaloid from the marine sponge-associated rare actinomycetes Kocuria sp. S42 - Jingwei Jia; Xiaozheng Wang; Jin Sang; Zhiyong Li; Shuangjun Lin; Zixin Deng; Tingting Huang (Natural Product Research, 2023)

Revealing maleic acid role in the preparation of α-hemihydrate gypsum from titanium gypsum through experiments and DFT calculations - Jingwei Du; Lin Tian; Manfu Qi; Chen Zhang; Hongfeng Di; Xiao Zhi; Jianping Zhu (Science of The Total Environment, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Effects of successional sulfadiazine exposure on biofilm in moving bed biofilm reactor: Secretion of extracellular polymeric substances, community activity and functional gene expression - Liang Zhu; Jingwei Ma; Huizhou Yuan; Lin Deng; Zhou Shi; Qiulai He; Shuizhou Ke (Bioresource Technology, 2023)

Competitive adsorption and immobilization of Cd, Ni, and Cu by biochar in unsaturated soils under single-, binary-, and ternary-metal systems - Zhuowen Meng; Shuang Huang; Jingwei Wu; Zhongbing Lin (Journal of Hazardous Materials, 2023)

Quantitative transport and immobilization of cadmium in saturated-unsaturated soils with the combined application of biochar and organic fertilizer - Zhuowen Meng; Shuang Huang; Wenting Mu; Jingwei Wu; Zhongbing Lin (Environmental Science and Pollution Research, 2023)

Evaluating traffic emission control policies based on large-scale and real-time data: A case study in central China - Chao Zou; Lin Wu; Yanan Wang; Shida Sun; Ning Wei; Bin Sun; Jingwei Ni; Jing He; Qijun Zhang; Jianfei Peng; Hongjun Mao (Science of The Total Environment, 2023)

Pollutant removal performance and microbial responses of pure moving bed biofilm reactor to the successional sulfadiazine exposure - Liang Zhu; Huizhou Yuan; Jingwei Ma; Lin Deng; Zhou Shi; Qiulai He; Shuizhou Ke (Journal of Water Process Engineering, 2023)

Experimental investigation of a novel sleeved member with additional friction dampers - Jingwei Gao; Chun-Lin Wang; Bin Zeng; Tianyi Qiu (Engineering Structures, 2023)

ZIF-67 loaded lotus leaf-derived biochar for efficient peroxymonosulfate activation for sustained levofloxacin degradation - Jingwei Yan; Lin Gong; Senyou Chai; Cong Guo; Wei Zhang; Hongyou Wan (Chemical Engineering Journal, 2023)

Production and Evaluation of a Novel Multi-Epitope Bivalent Vaccine Against Echinococcus multilocaularis Metacestode - Runle Li; Mingyuan Xin; Kunmei Liu; Bingwen Hu; Jingwei Ma; Pei Zhou; Lin Feng; Mingquan Pang; Ri-li Ge; Haining Fan; Le Guo; Feng Tang (International Journal of Peptide Research and Therapeutics, 2022)

Characterization, risk assessment and resource potential of sediments in the black-odor water in Hunan, China - Jingwei Ma; Xiao Lin; Zefang Yu; Xiang Wang; Jiyi Chen; Qiulai He (Environmental Monitoring and Assessment, 2022)

Molecular characterization and gene expression analysis of tomato WOX transcription factor family under abiotic stress and phytohormone treatment - Hui Li; Xiaohong Li; Meihua Sun; Shuisen Chen; Hui Ma; Jingwei Lin; Yibo Sun; Ming Zhong (Journal of Plant Biochemistry and Biotechnology, 2021)

Genetic basis of maize ear angle revealed by high-density single nucleotide polymorphism markers in four recombinant inbred line populations - Jingwei Lin; Shoukun Li; Gengyuan Liang; Meiling Liu; Taicheng Jin; Zhengwei Qu; Haoge Li; Shuisen Chen; Cong Li; Ao Zhang; Yanye Ruan; Zhenhai Cui (Euphytica, 2020)

Quantitative proteomics analysis reveals the tolerance of Mirabilis jalapa L. to petroleum contamination - Shuisen Chen; Hui Ma; Zhifu Guo; Yaping Feng; Jingwei Lin; Menghua Zhang; Ming Zhong (Environmental Science and Pollution Research, 2017)

Isolation and Analysis of Salt Response of Lactobacillus plantarum FS5-5 from Dajiang - Xuefei Song; Qianqian Wang; Xin Xu; Jingwei Lin; Xiaorui Wang; Yating Xue; Rina Wu; Yingfeng An (Indian Journal of Microbiology, 2016)

Dielectric barrier discharge plasma induced degradation of aqueous atrazine - Jingwei Feng; Lin Jiang; Dan Zhu; Kuizu Su; Dayong Zhao; Jibiao Zhang; Zheng Zheng (Environmental Science and Pollution Research, 2016)

Improving arsenic mobility concentration from As-polluted soils by the functional strains - JianFeng Bai; XianGui Lin; Jue Dai; JianFeng Hua; Hua Qin; JunLi Hu; YiMing Wang; ChengLong Zhang; JingWei Wang; WenYi Yuan (Science China Earth Sciences, 2015)

Galectin-3 contributes to cisplatin-induced myeloid derived suppressor cells (MDSCs) recruitment in Lewis lung cancer-bearing mice - Tian Wang; Zhaohui Chu; Hao Lin; Jingwei Jiang; Xinli Zhou; Xiaohua Liang (Molecular Biology Reports, 2014)

Glutathione transferase T1 and M1 genotype polymorphism in the normal population of Shanghai - Jianhua Shen; Goufang Lin; Wuxing Yuan; Jingwei Tan; Hermann M. Bolt; Ricarda Thier (Archives of Toxicology, 1998)